Recherches archéologiques tuniso-françaises à Rougga. - Euzennat, Maurice,; Slim, Hédi, (Archaeology of the Maghreb ;, 2020)
Located in Byzacena, 12km south-east of Thysdrus/El Jem, the municipality of Bararus/Henchir, Rougga is known for its large Roman cisterns first reported in the 18th century and for the discovery of a hoard of Byzantine gold coins. This volume gives an account of the results of excavations carried out at the site of the forum, from 1971-1974.